Liquid crystals as pore template for sulfated zirconia - Moris, Carlos Henrique A. A. [UNESP]; Alves-Rosa, Marinalva A. [UNESP]; Freitas, Fernanda G. [UNESP]; Martins, Leandro [UNESP]; Santilli, Celso [UNESP]; Pulcinelli, Sandra H. [UNESP] (Elsevier B.V., 2020)
Porous sulfated zirconia was prepared using a sol-gel process associated with liquid crystal templates (LCTs). Evaluation was made of the e ffects of the Zr 4+ :SO 4 2 - molar ratio and aging time on the formation and stability of the lyotropic arrangement of the LCT gel and the features of the resulting mesoporous powders. Polarized light microscopy and small -angle X-ray di ffraction (SAXD) analysis of the LCT gel revealed the prevalence of hex- agonal mesophase ( P6mm ) in the sulfated samples. Thermal treatment of the samples resulted in sulfated ZrO 2 ceramic powders whose infrared spectra exhibited bands characteristic of mono- and bi-dentate SO 4 2 - groups bonded to ZrO 2 . X -Ray di ffractograms of the materials showed a mixture of monoclinic and tetragonal phases of zirconia, with the tetragonal phase increasing from 86 -90% to 100% as the Zr 4+ :SO 4 2 - molar ratio decreases from 15 to 5. Crystallite sizes of about 9.5 and 4.5 nm were observed for the pristine and sulfated zirconia (Zr 4+ :SO 4 2 - = 5), respectively. The lattice fringe distances observed for selected areas in the electron di ffrac- tion patterns and in high -resolution transmission electron micrographs con firmed the mixture of tetragonal and monoclinic crystalline phases. Small -angle X -Ray scattering analysis showed that the gyration radius was around 2 nm and that the particles were organized as a branched network with a fractal surface when sulfate was inserted in the zirconia structure, improving its porous characteristics. The LCT generated pores with greater diameters (up to 4.4 nm) in the sulfated samples, while the surface area increased to 146 m 2 g -1 . The gel aging process led to the reinforcement of the pore wall structure, prevented shrinkage e ffects during calcination, and enabled higher surface areas to be achieved. Scanning and transmission electron microscopy analyses showed that the walls of the pores were composed of platelets of irregular shapes, giving rise to mesopores. The porous structure, combined with the presence of acid sites, improved by sulfate groups at the surface of tetragonal zirconia crystallite, makes these materials promising candidates for application as catalysts in dehydration re- actions.
Keywords: Sulfated zirconia; Liquid crystal template; Porous materials; Sol-gel process; Catalyst